CFD parametric study of thermal performance of different fruit packaging box designs - Ilangovan, Adhiyaman (2022)
Air temperature and relative humidity values of cold storage conditions are the major factor affecting the perishability of fresh fruits. The sooner the field heat is extracted from the products and the proper temperature is maintained consistency throughout the cold chain, larger it will be shelf life of these products. Forced air cooling is the most commonly used technique to remove the field heat in post-harvest storage. Energy-efficient and quality-oriented cold storage mainly depends on the time to remove the heat. This time can be reduced by optimizing the configuration of the vent holes of the packaging box, namely it dimension (area), it shape, alignment and position. This paper shows the numerical predictions of air temperature and velocity by a CFD parametric study of eight different vent hole configurations. These configurations consider a packaging box with double wall. The vent holes of each wall have different dimension and shape. The vent holes of both walls can be also aligned or unaligned. The analysis of results aims to determine the best configurations that improve the cooling rate, the airflow and temperature uniformity. The numerical predictions of the air temperature show close values, but three configurations can be identified as predicting the lowest air temperature values with lowest standard deviation. These results may help on the development of new configuration for fruit boxes that promote the extension of the fruits shelflife.